IMPLEMENTASI PELAYANAN PUBLIK BAGI PASIEN BPJS KESEHATAN DI RSUD DR. RM PRATOMO KOTA BAGNSIAPIAPI KABUPATEN ROKAN HILIR - Pegi Melati Br. Sembiring; Dessy Artina; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
It can be said that the implementation of public services for patients withBPJS health insurance at RSUD Dr. RM Pratomo is good, but it has not reachedthe minimum service standards expected based on Rokan Hilir Regent RegulationNumber 35 of 2018 concerning Service Standards for the Regional GeneralHospital dr. RM Pratomo Bagansiapiapi City. The main problems in this studyare: How is the implementation of public services for BPJS patients at RSUD Dr.RM Pratomo, Bagansiapiapi City; what are the supporting and inhibiting factorsin the implementation of public services provided by the hospital to patients; andwhat efforts have been made by the hospital to improve the quality of publicservices to make it better. This type of research is a type of sociological legalresearch carried out at Dr. RM Pratomo Hospital, Bagansiapiapi City, the datasources used are primary data sources and secondary data sources. Datacollection techniques carried out in this study were observation, interviews,questionnaires and literature. Data were analyzed using qualitative methodswhich produced descriptive data and were concluded with deductive thinkingmethod.The results showed that the implementation of RSUD Dr. RM Pratomo canbe said to be good, but has not reached the expected minimum service standards.One of the supporting factors in the implementation of services is the existence ofbudgetary assistance from the government, education and training of humanresources and so on. In addition, the inhibiting factors can be in the form offacilities and infrastructure, low public knowledge regarding the BPJS flow, andthe large number of patients seeking treatment. Therefore, the efforts made are tomaintain and complete the facilities and infrastructure, patient family violence,and socialization related to the health BPJS flowKeywords: Implementation of public - Health BPJS –RSUD Dr. RM Pratomo